Shail Mayaram. Resisting Regimes: Myth, Memory, and the Shaping of Muslim Community. Delhi: Oxford University Press, 1997. xiv, 298 pp. - Dube, Saurabh; Franco Toriz, Germán (Estudios de Asia y África, 2000)
-